1998
DOI: 10.1046/j.1365-2427.1998.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in the epilithic biofilm of an acid stream

Abstract: Summary 1. The extent of spatial and temporal variation, and the taxonomic and biochemical composition of epilithic biofilm were determined in a first‐order, acidic stream in the Ashdown Forest, southern England. 2. The biofilm had an autotrophic component consisting of acidobiontic diatoms, small coccoid green algae, zygnematacean filamentous green algae, and a heterotrophic component of bacteria. Fungi were absent. 3. Diatoms were the dominant algal group in spring. These were succeeded by coccoid green alga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 68 publications
3
68
0
Order By: Relevance
“…In the present study, NFE accounted for 53.28-54.44% (Table 4). Ledger and Hildrew (1998) reported 29-33% carbohydrate in periphyton developed on stones. Nielsen et al (1997) observed that the extra-cellular polymeric substances in biofilms are responsible for 50-80% of total organic matter and therefore, large amounts of carbohydrate, which explains the high proportion of carbohydrates in periphyton.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, NFE accounted for 53.28-54.44% (Table 4). Ledger and Hildrew (1998) reported 29-33% carbohydrate in periphyton developed on stones. Nielsen et al (1997) observed that the extra-cellular polymeric substances in biofilms are responsible for 50-80% of total organic matter and therefore, large amounts of carbohydrate, which explains the high proportion of carbohydrates in periphyton.…”
Section: Discussionmentioning
confidence: 99%
“…Algal biomass is affected by stone location in streams (Matthaei et al, 2003) and algal biomass generally increases with stone size (Ledger and Hildrew, 1998). At the scale of individual stones, orientation and exposure to stream flow affect algal biomass accumulation (Stevenson, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The scrubbed surface of each cobble was carefully traced onto an acetate sheet and the area (cm 2 ) subsequently determined from the mass of the tracings (Ledger & Hildrew, 1998). The biofilm samples were later defrosted in the laboratory and made up to 24 ml with water.…”
Section: Algal Biomass Determinationmentioning
confidence: 99%
“…The biofilm samples were later defrosted in the laboratory and made up to 24 ml with water. Estimates of ash-free dry mass (AFDM) were made by placing aliquots of biofilm slurry (5-10 ml) in crucibles for ashing at 500°C for 4 h. AFDM was estimated as the difference between oven-dried (80°C) and ashed crucibles (Ledger & Hildrew, 1998).…”
Section: Algal Biomass Determinationmentioning
confidence: 99%